Attributes of Non-Formal Learning Amongst Malay Adults in Malaysia - Mat Junoh, Adanan (2006)
The purpose of this study is to identify non-formal learning attributes in the community amongst adults in Malaysia guided by the following research questions: (1) What is the profile of adult learners? (2) What are the non-formal learning patterns? (3) Why do the Malay-Muslims participate in non-formal learning? (4) Why do rural community participate in non-formal learning? (5) Why is religion the main learning content? and (6) Why are mosques the main venues for learning? The study combined quantitative and qualitative methods based on the sequential multi method design. Quantitative method was used specifically for inquiring into first and the second research questions. Qualitative method was employed to address third to sixth research questions. The quantitative sampling comprised of 3000 respondents aged twenty-one years old and above. Four states namely Kedah, Terengganu, Selangor and Melaka were selected as the locations of the study. Trained enumerators collected data using a set of questionnaire. The data were analyzed using the SPSS program. For the qualitative phase, the researcher conducted a case study at Kampung Kurnia, Kluang, Johor. Eight participants selected using the snowballing sampling technique were interviewed. The study indicates that learners’ profile is Muslim-Malay, non–married middle age, rural community, with lower education level and income. Participation by both genders is about the same. The learners possess a positive attitude towards learning and a high self–esteem. The study also shows that religion is the primary learning content and house of worship as the major learning site, provider and sponsor. Most non-formal learning is free. Majority of the learners spend one to two hours daily for their learning. Acquiring knowledge and serving the community are the primary motives participating in learning. Time and work constraints are the primary learning problem. Based on the case study, participation of Malay-Muslims and rural community is influenced by the religion, values and culture. Religion becomes a major learning content to fulfill the religious obligation and inadequacy feeling of religious knowledge. The mosque is the main learning site because of the influence of religion, values and culture as well as being an important social institution. The study concludes that adult learners for the non-formal learning come from various socio-demographic backgrounds. Attributes and participation in the learning influenced by contextual factors of religion and culture.